Feline congestive heart failure : mortality rate and survivability and determination of clinical efficacy of pimobendan as alternative therapy - Xi, Jessie Bay Ji (2018)
The occurrences of heart disease in cats had increased with the availability of echocardiography. These patients are often presented with congestive heart failure, feline aortic thromboembolism and sudden death. In this study, the objectives were; 1) to determine the mortality rate and survivability of cats diagnosed with congestive heart failure and, 2) to correlate the clinical progressions and outcomes of cats diagnosed with congestive heart failure that were treated with pimobendan. Information on cats presented at the University Veterinary Hospital, Universiti Putra Malaysia that were diagnosed with cardiac diseases were collected and the cat owners were contacted for follow-ups on the cats’ heart condition. The modified New York Medical Associate classification was used to stage the cats’ heart condition. The mortality rate and survivability was determined using the Kaplan-Meier estimator. Cats that showed no improvement after treatment with diuretics-ACE inhibitor combination were recruited and treated with pimobendan for two months. The clinical efficacy of the drug was monitored based on observation of clinical signs, measurement of serum cardiac troponin concentrations, blood pressure monitoring, radiography, and echocardiography. Data obtained was analysed using paired T-test and One-way ANOVA to determine the effect of pimobendan pre- and post-treatment during the 2 months therapy. As a conclusion, the mortality rate determined was 26.7% and the there was no survival benefit for the cats with compliant owners (p > 0.05) despite the class of the feline cardiac patients grouped into. Pimobendan treatment was beneficial for cats diagnosed with dilated cardiomyopathy and restrictive cardiomyopathy. Administration of pimobendan in cats with hypertrophy cardiomyopathy has to be monitored closely.